ANXIETY OF NICK O'BANON TO FACE THE DEATH REFLECTED IN DAVID R. ELLIS'S MOVIE FINAL DESTINATION 4 (2009): A PSYCHOANALYTIC APPROACH - ROSANTI, IKA RATNA (2010)
The object of this research is the movie entitled Final Destination 4 by David Richard Ellis. The major problem of this study is how is anxiety of Nick O'Banon to face the death reflected in film Final destination 4 is based on Psychoanalytic approach. It occurs because he has a horrific intuition in which a sequence of event occurs that causes many race cars to crash leading to flaming debris that brutally kills his friends and the upper stand collapses on him eventually killing him. This study is qualitative study. The object of the study is Final Destination 4 movie directed by David R. Ellis and written by Eric Bress published in 2009 in Florida by The New Line Cinema. The data sources are divided into two namely primary data source and secondary data source. The primary data source is the film itself and the secondary data source is the other sources related to the analysis such as references, author's biography, criticisms relation to the problems and material related to the study whether picking up from books or internet. The methods of data collection are observation and library research. The technique of data analysis is descriptive analysis. Based on the analysis, the writer concludes that the problems of the major character cause the conflict of his mental condition. It happens when there is contradiction between Id, Ego, and Superego and it brings him into anxiety